Measuring Pro- and Anti-Inflflammatory Biomarkers Among Low-Income Hispanic Adults: A Feasibility and Pilot Assessment - Charles F. Hodgman; Emily C. LaVoy; Craig Johnston; Ezemenari Obasi; Rosenda Murillo; Sandra Yan; Daniel P. O'Connor; Lorna McNeill; Lorraine R. Reitzel; Daphne C. Hernandez (New Prairie Press, 2022)
Using the Orsmond and Cohen feasibility framework, the primary aim of this study was to assess the feasibility of the implementation of recruitment strategies, data collection procedures, and managerial resources needed to assess pro- and anti-inflammatory biomarkers from low-income, younger Hispanic adults. The secondary aim of this study was to describe the relationship between discrimination stress and inflammation as pilot work for future studies. Data were collected in a Houston-area community center from self-identifying Hispanic adults (ages 21-35) (August 2018). Inflammation was evaluated from blood samples, and interviewer-administered surveys in participants' preferred language measured discrimination stress (Hispanic Stress Inventory-2 discrimination subscale). Spearman rank-order correlations evaluated the relationships between discrimination stress and inflammatory biomarkers. The recruitment strategies, data collection strategy, and the associated resources were evaluated and found to be feasible. While 50 participants consented to donate blood, five were too dehydrated for sample collection. Among the 45 participants [Mage = 28.9 (SD = 4.4), 17.8% U.S.-born, 42.2% 1.5 generation, 40% 1.0 generation], discrimination stress was negatively correlated with proinflammatory cytokine interleukin-8 (p < 0.01). This study demonstrated feasibility using established benchmarks. The negative correlation between discrimination stress and interleukin-8 suggests discrimination stress may contribute to inflammatory dysregulation.